Situated learning among business entrepreneurs in Sarawak - Norhasmala, Mashor (Universiti Malaysia Sarawak (UNIMAS), 2015)
The emergence of situated learning is seen as a part of scholarly attention and academic curiosity. There is a significant increase in numbers of key research done pertinent to situated learning in order to explore and validate the elements of situated learning. However, a crucial query in this field remains that of how business entrepreneurs actually learn. The current study aims to offer an explanatory understanding into the situated learning of business entrepreneur in Sarawak context. Qualitative case study supported the exploration for real-life experiences of business entrepreneurs in Sarawak.. The findings of this study revealed that, there are seven first learning steps to do business; selling for fun during university, seek information from the internet, attending courses, learning from home, self-experience by working with employer, getting business experience from family members and life experience. Basically, this study concluded that, situated learning is a vibrant process that occurs by socialization, collaboration and interaction experiences among business entrepreneurs in Sarawak during their entrepreneurial voyages.